An other kingdom departing the consumer culture - Block, Peter 1939-; Brueggemann, Walter 1933-2025; McKnight, John 1931- (Wiley, 2016)
"Our seduction into beliefs in competition, scarcity, and acquisition are producing too many casualties. We need to depart a kingdom that creates isolation, polarized debate, an exhausted planet, and violence that comes with the will to empire. The abbreviation of this empire is called a consumer culture. We think the free market ideology that surrounds us is true and inevitable and represents progress. We are called to better adapt, be more agile, more lean, more schooled, more, more, more. Give it up. There is no such thing as customer satisfaction. We need a new narrative, a shift in our thinking and speaking. An Other Kingdom takes us out of a culture of addictive consumption into a place where life is ours to create together. This satisfying way depends upon a neighborly covenant--an agreement that we together, will better raise our children, be healthy, be connected, be safe, and provide a livelihood. The neighborly covenant has a different language than market-hype. It speaks instead in a sacred tongue. Authors Peter Block, Walter Brueggemann, and John McKnight invite you on a journey of departure from our consumer market culture, with its constellations of empire and control. Discover an alternative set of beliefs that have the capacity to evoke a culture where poverty, violence, and shrinking well-being are not inevitable--a culture in which the social order produces enough for all. They ask you to consider this other kingdom. To participate in this modern exodus towards a modern community. To awaken its beginnings are all around us. An Other Kingdom outlines this journey to construct a future outside the systems world of solutions"--
Machine generated contents note: Signs of the Times Introduction: Context Is Decisive The Landscape of the Market World Enclosure Covenantal versus Contractual Order The Neighborly Covenant Chapter 1. The Free Market Consumer Ideology Scarcity Certainty and Perfection Privatization The Institutional Assumptions Better Management/Technology Is the Fix Interpersonal Is a Problem Competition Trumps Trust Toward a Neighborly Culture A Culture Based on Covenant Chapter 2. Neighborly Beliefs Abundance Mystery Mystery at Work A Place for God Holiness Wilderness Fallibility Failing to Be God Grief The Common Good Chapter 3.
Enough Is Enough: Limits of the Market Ideology The Consumer Market Disciplines Surplus Predictability and Control Speed and Convenience The Blanket of Technology The Sale of Convenience Convenience Displaces Capacity Digital Solutions The Meaning of Money Money and the Machine Wishing for Safety, Believing in Growth Competition and Class Class by Design Class Warfare and the Distribution of Wealth The Myth of Individualism Chapter 4. Tentacles of Empire The Corporatization of Schools No View from the Top End of Aliveness Mobility and Isolation Un-Productive Wealth Violence Illusion of Reform Chapter 5. The Common Good Is the New Frontier The Neighborly Covenant The Commons An Alternative Social Order Resisting the Empire Off-Market Possibilities The Neighborly Way The Alternative to Restless Productivity The Shadow Side of Community Chapter 6.
The Disciplines of Neighborliness Time A Time for All Things Time Is the Devil Standing in Line Kairos Food Food and Sacred Re-Performance The Local Food Movement Food and Culture Silence Listening Quakers and Time and Listening Sacraments of Silence Covenant: A Vow of Freedom and Faithfulness Covenant and Retributive Justice The Right Use of Money Money and Our Affection for Place A Liturgy for the Common Good Prophetic Possibilities Story as Liturgy and Re-performance The Re-Performing Power of Liturgy Postscript: Beyond Money and Consumption Timing Is Everything Signs of Change Commentaries References and Further Reading Acknowledgments Index About the Authors
Includes bibliographical references and index
Keywords: POLITICAL SCIENCE / Public Policy / Social Services & Welfare; SOCIAL SCIENCE / Human Services; BUSINESS & ECONOMICS / General; SOCIAL SCIENCE / Sociology / General; Community development; Community life; Neighborliness; Wirtschaft; Solidarische Ökonomie; Nachbarschaftshilfe; Gemeinwesen; Gemeindeentwicklung; Nachbarschaft